The determination of the validity of an application-based knee-training device. Issue 5 (20th October 2019) - Horstmann, Hauke; Krost, Eva; Welke, Bastian; Kerling, Arno; Hanke, Alexander; Jakubowitz, Eike; Weber-Spickschen, Thomas Sanjay
ABSTRACT: The goals of knee rehabilitation are to improve range of motion and muscle status. The aim of the study was to investigate accuracy and reproducibility of a newly designed knee-training device (KT) under standardized laboratory conditions. Two application-based software programs, one to measure maximum force and the other intended to improve users' coordination were developed to be used on a tablet during exercises, wirelessly connected to KT placed under the popliteal fossa. KT was loaded for 20 intervals of 15 seconds (s) ranging between 0–350 Newton (N) each. The interval of times was chosen to be enough to take right measurement for accurate results. In addition, a 300-s continuous measurement was undertaken. The pressure readings were developed through a servo-hydraulic system and used as reference values. KT results were compared with the reference values to assess its accuracy. In addition, KT was tested on a force-measuring platform in a close to reality measurement. Based on Bland-Altman plots, the mean difference between KT and material testing machine was −0.63 N (0.4%), between KT and force-measuring platform was −0.11 N (0.7%), which proves the accuracy of its result. Laboratory experiments confirm that KT delivers precise and reproducible values, which provide base for clinical trials.